An accurate algorithm of PMU-based wide area measurements for fault detection using positive-sequence voltage and unwrapped dynamic angles - Muhammad Qasim, Khan; Musse Mohamud, Ahmed; Ahmed Mohamed, Ahmed Haidar (Elsevier, 2022)
Modern power system requires advanced and intelligent sensors-based protection such as a Phasor Measurement Unit that can provide faster, accurate, and real-time data acquisition. The aim is to allow accurate action-based performance for analysts in monitoring the transmission lines so that rapid actions can be taken during abnormal circumstances before the blackout occurs. Among different algorithms, this study focuses on modelling the non- recursive phasor estimation method in a power Simulink environment for a standard test system equipped with a developed algorithm to detect the fault zone. The algorithm includes an index for faulty bus classification based on the positive-sequence voltage measurements of the pre-fault and post-fault conditions, where the bus with a maximum differential percentage is identified as a faulted bus. An important differentiation of this work is that the proposed algorithm can coordinate with all phasor measurement units to accurately determine the faulty line using the index of unwrapped dynamic phase angles. Furthermore, the robustness of the indices is analyzed in the presence of sudden load change, measurement noise, and during nonlinear high-impedance faults. The performance of the comprehensive algorithm is investigated on the IEEE 9-bus and 39-bus standard test systems by applying different faults scenarios, considering several factors such as fault inception angles, line-fault resistance, ground-fault resistance. The comparative studies have shown that the proposed indices can play a significant role in segregating the fault and non-fault conditions, as they are needed to supervise the appropriate relays for enhancing the overall security of the power grid.